Cooperative interaction between the MUC1-C oncoprotein and the Rab31 GTPase in estrogen receptor-positive breast cancer cells. - Caining Jin; Hasan Rajabi; Sean Pitroda; Ailing Li; Akriti Kharbanda; Ralph Weichselbaum; Donald Kufe (PLoS ONE, 2012)
Rab31 is a member of the Ras superfamily of small GTPases that has been linked to poor outcomes in patients with breast cancer. The MUC1-C oncoprotein is aberrantly overexpressed in most human breast cancers and also confers a poor prognosis. The present results demonstrate that MUC1-C induces Rab31 expression in estrogen receptor positive (ER+) breast cancer cells. We show that MUC1-C forms a complex with estrogen receptor α (ERα) on the Rab31 promoter and activates Rab31 gene transcription in an estrogen-dependent manner. In turn, Rab31 contributes to the upregulation of MUC1-C abundance in breast cancer cells by attenuating degradation of MUC1-C in lysosomes. Expression of an inactive Rab31(S20N) mutant in nonmalignant breast epithelial cells confirmed that Rab31 regulates MUC1-C expression. The functional significance of the MUC1-C/Rab31 interaction is supported by the demonstration that Rab31 confers the formation of mammospheres by a MUC1-C-dependent mechanism. Analysis of microarray databases further showed that (i) Rab31 is expressed at higher levels in breast cancers as compared to that in normal breast tissues, (ii) MUC1+ and ER+ breast cancers have increased levels of Rab31 expression, and (iii) patients with Rab31-positive breast tumors have a significantly decreased ten-year overall survival as compared to those with Rab31-negative tumors. These findings indicate that MUC1-C and Rab31 function in an autoinductive loop that contributes to overexpression of MUC1-C in breast cancer cells.